ASPEK MANAJEMEN - Ade Aulia Riski; Afsah Sandy Tarigan; Said Agil Lubis; Dini Vientiany (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This study aims to examine the fundamental differences between Sharia management and conventional management in terms of philosophy, principles, and their application in organizations. Sharia management integrates Islamic spiritual and ethical values, such as honesty, justice, responsibility, and consultation, based on the Quran and Hadith. This approach focuses not only on material profit but also on social welfare and sustainability. In contrast, conventional management prioritizes efficiency and productivity without explicitly incorporating spiritual values. This study provides a deeper understanding of the application of Sharia principles in management functions and its impact on organizational ethics and sustainability. The findings show that Sharia management can foster more ethical and sustainable organizations, making it relevant for organizations focused on social welfare and long-term profit